KARAKTERISTIK KEPEMIMPINAN DALAM PENGELOLAAN LEMBAGA PENDIDIKAN ISLAM SWASTA (STUDI KASUS DI SD ISLAM AL MUTTAQIN) - Febrina, Rifka; Yani, Nurmaningsih; Hutabarat, Rinto; Asmendri, Asmendri (STKIP Pesisir Selatan, 2025)
In Islamic educational institutions, the role of leaders has a very strategic position in realizing the institutional vision. Leadership is a key element that drives the dynamics of an institution or organization. A leader is required to have the ability to anticipate change, manage resources effectively, and direct organizational strategies in realizing the institutional vision, especially in terms of developing institutional quality, improving the quality of human resources, and strengthening competitiveness in various sectors. The quality of leadership significantly affects the direction and achievement of institutional goals. This study aims to explain the characteristics of leadership in the management of private Islamic educational institutions through a case study at SD Islam Al Muttaqin. This study uses a descriptive qualitative approach and case study method. This study explains the characteristics of effective leadership in Islamic educational institutions emphasizing Islamic values ​​such as monotheism, Amanah and responsibility and deliberation. Supporting factors in leadership are communication, work motivation, exemplary behavior and reward-punishment systems. The results of the study indicate that the success of the institution is greatly influenced by the quality of visionary, fair, and inspiring leadership in managing resources and involving all elements of the school.